PENGARUH PERSEPSI RISIKO DAN PENGETAHUAN MAHASISWA TERHADAP MINAT INVESTASI SAHAM SYARIAH - Cindy Claudia; Efni Anita; Nurlia Fusfita (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine and analyze how much influence the perception of risk and knowledge of students on interest in Islamic stock investment in students of the Faculty of Economics and Islamic Business, Sulthan Thaha Saifuddin State Islamic University Jambi. This study uses a quantitative approach to the data analysis method of Multiple Linear Regression. The results show that the perception of risk (X1) has no significant effect on investment interest (Y), so it can be concluded that Ha is rejected and H0 is accepted. Knowledge (X2) shows a significant effect on investment interest (Y), so it can be concluded that Ha is accepted and H0 is rejected. Meanwhile, risk perception (X1) and knowledge (X2) simultaneously have a significant effect on investment interest (Y), so it can be concluded that Ha is accepted and H0 is rejected. The influence of these two variables is 41.1% while the remaining 58.9% is influenced by other variables outside this study.